A note on the estimation of long-run relationships in panel equations with cross-section linkages - Francesca Di Iorio; Stefano Fachin (Kiel Institute for the World Economy (IfW), 2012)
We address the issue of estimation and inference in dependent non-stationary panels of small cross-section dimensions. The main conclusion is that the best results are obtained applying bootstrap inference to single-equation estimators, such as FM-OLS and DOLS. SUR estimators perform badly, or are even unfeasible, when the time dimension is not very large compared to the cross-section dimension.
Keywords: C15; C23; C33; 330; Panel cointegration; FM-OLS; FM-SUR; DOLS; DSUR